PENGARUH MOBILISASI SENDI DENGAN KONSEP MULLIGAN MEDIAL DAN LATERAL GLIDE TERHADAP KEMAMPUAN FUNGSIONAL PENDERITA OSTEOARTHRITIS KNEE PADA LANSIA DI STPL BEKASI - Achirda, Nur; Ali, Mohammad; Anggita Lisdianti, Rossa (Jurnal Fisioterapi dan Kesehatan Indonesia, 2023)
ABSTRACT Elderly is a condition that will be experienced by every human being. The elderly will experience an aging process where the elderly will experience some decline in body functions, one of which is the musculoskeletal system. The elderly will experience a decline in functional abilities caused by degenerative diseases, one of which is osteoarthritis. Joint mobilization with the Mulligan Medial and Lateral Glide concept is a manual therapy technique that can treat joint pain, stiffness and joint dysfunction which can improve functional ability. This research is quasi-experimental with the design of the Two Group Pre Test and Post Test Design. The sample was selected by purposive sampling method and the number of samples for each group was 12 people in the treatment group and the control group. The tool for measuring functional ability uses the Knee Injry Osteoarthritis Outcome Score (KOOS) questionnaire. Paired T-Test with 95% confidence level and Independent Sample T-Test. After being given the intervention, the results obtained in the treatment group and control group using the Paired Sample T-Test obtained a p-value of 0.000. The results of the Independent Sample T-Test obtained a p value of 0.000, the mean result of the Independent Sample T-Test in the treatment group was 22.58 while the mean result in the control group was 13.27. The results of this study can be concluded that joint mobilization using the Mulligan concept affects the functional abilities of patients with knee osteoarthritis in the elderly. Keywords: Mobilization of joints with the concept of Mulligan Medial and Lateral Glide; Functional Ability; Knee Osteoarthritis;